Current advances on titanate glass-ceramic composite materials as waste forms for actinide immobilization: A technical review. Issue 5 (May 2022) - Zhang, Yingjie; Kong, Linggen; Ionescu, Mihail; Gregg, Daniel J.
Graphical abstract: A comprehensive review of the current advances on titanate glass-ceramic composite materials as waste forms for actinide immobilization is given. Apart from providing a comprehensive summary of earlier works in the field, some technical analysis and perspectives are provided pointing to the potential future studies. Highlights: A comprehensive review on titanate glass-ceramic waste forms for actinide immobilization is provided. Current advances on the titanate glass-ceramic composite materials are summarised. Abstract: As the emerging versatile waste forms for immobilizing actinide-rich radioactive wastes, glass-ceramic composite materials based on some durable ceramic phases are being developed. They have apparent advantages over the conventional borosilicate glasses and multi- or single- phase ceramics as they essentially combine the chemical and processing flexibilities of glasses to accommodate processing impurities and excellent chemical durability of ceramic phases to host actinides. More recently, some new advances have been made on scientific and technological aspects including new glass-ceramic systems; improved understanding of ceramic phase evolution in glass; actinide validation studies and simplified processing techniques. This review is intended to cover the current advances on the development of glass-ceramic composite waste forms focusing on titanate ceramic phases (zirconolite, pyrochlore and brannerite) for immobilizing various actinide-rich radioactive wastes arising from the nuclear fuel cycle.